Bending deformation of bio-tensegrity model at different deployable schemes / Nur Syakinah Anuar ... [et al.] - Anuar, Nur Syakinah; Md Yunus, Balqis; Saari @ Ash’ari, Nadiah; Syed Yahya, Syed Muhammad; Oh, Chai Lian (2024)
Tensegrity structures consist of multiple struts or cables that are interconnected and ideal for deployable structures. Given the challenges of controlling the strut’s deformation, active cables are more preferred and commonly studied in the deployment of tensegrities. The selection of the active cables becomes important as the deployment of tensegrities is highly dependent on the construction cost and computational time. This paper presents three different deployable schemes considering different sets of active cables. The deployable schemes were studied in this study to investigate the bending deformation of a human spine-inspired bio-tensegrity model. The shape change strategy involves a computational approach based on sequential quadratic programming to optimise the cable force elongation. A total of nine shape change analysis cases were conducted on the bio-tensegrity model to undergo deformation under three different schemes and three uni-directional targeted coordinates. The bending ability of bio-tensegrity models, the convergence curve, and axial forces were all discussed. It was found that the deployment scheme S3 is the most efficient scheme for the model to achieve different targets in uni-directional mode. This study is useful for applications such as deployable structures, automation, and robots.